BIOLOGICAL SCREENING OF CRUDE EXTRACT OF PENICILLIUM SP. EU0013 - Kalsoom; H. U. Shah; Z. Iqbal (Journal of Animal and Plant Sciences, 2017)
Medicinal plants and microbe are a rich source of secondary metabolites. The aim of the current work was to isolate the crude extract from Penicillium sp. EU0013 and study its antimicrobial potential at Natural Products Laboratory, The University of Agriculture Peshawar. Fermentation of Penicillium EU0013 was carried out using potato dextrose broth. The yield of crude ethyl acetate extract was calculated 1gmL-1 from static flask fermentation. The fungal extract was screened for bench-top bioassays including antifungal, antibacterial, phytotoxic, insecticidal and nematicidal activities. Results showed that at 100, 200 and 300 µg.mL-1 the extract exhibit antibacterial activity ranging from 13.4 to 80.7mm against E. coli, Bacillus subtilis,  Xanthamonas sp. and Proteus vulgaris, and 14.3 to 80.7 mm against Aspergillus flavus, Alternaria alternata, A. niger and Fusarium oxyspourm. The phytotoxic, insecticidal and nematicidal activity on 7thday, 24 hour and again 7 days of Penicillium extract increased with increased of dose with highest mortality of 16.6, 63.32 and 85.75 % at 200, 200 and 100 μg. mL-1 respectively.
Keywords: Penicillium sp.EU0013; natural products; bioassays; phytotoxic; antibacterial; antifungal activities